Effect of repeat manual blood pressure measurement on blood pressure and stage of hypertension. Issue 4 (2nd October 2019) - Rhodehouse, Bryce C.; Fan, Jerry; Chen, Wencong; McNeal, Michael J.; Durham, Charis G.; Erwin, John P.
Abstract: Hypertension management guidelines are influenced by clinical trials that utilize automated office blood pressure (BP) to measure BP. Many primary care clinics still use manual office BP, which has been shown to produce significantly higher BP values than automated office BP. In a primary care office, a manual BP was obtained by nursing staff using an aneroid sphygmomanometer. Initial BPs ≥120/80 mm Hg were repeated during the clinical encounter by the physician. A total of 1012 encounters were analyzed, with 1000 meeting inclusion criteria. The median difference between nurse and provider BP was 4 mm Hg in systolic BP and 2 mm Hg in diastolic BP ( P < 0.0001), with the greatest difference seen in patients with initial BPs >150 mm Hg systolic (10 mm Hg; P < 0.0001). Repeating BP measurements resulted in 34% of patients being reclassified to a lower hypertension stage. Patients with stage 1 and 2 hypertension initially were reclassified as controlled (systolic BP <130 mm Hg) in 40% and 8% of encounters, respectively, with repeat measurements. In clinics that use manual office BP, repeating a manual BP by the physician may provide a better reflection of adherence to standard hypertension performance measures used in the primary care setting.